2022
DOI: 10.3389/fimmu.2022.1038086
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomics reveals early, broad release of chemokine, cytokine, TNF, and interferon mediators following trauma with delayed increases in a subset of chemokines and cytokines in patients that remain critically ill

Abstract: Severe injury is known to cause a systemic cytokine storm that is associated with adverse outcomes. However, a comprehensive assessment of the time-dependent changes in circulating levels of a broad spectrum of protein immune mediators and soluble immune mediator receptors in severely injured trauma patients remains uncharacterized. To address this knowledge gap, we defined the temporal and outcome-based patterns of 184 known immune mediators and soluble cytokine receptors in the circulation of severely injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…A common limitation seen in crevicular fluid proteomics is the lack of identification of cytokines, which was often explained by the low absolute abundance of these proteins [12,14]. Targeted approaches may be appropriate for the direct identification of these cytokines, yet DIAbased approaches have also proven to be suited for deeper proteome coverage, especially in cases of high dynamic ranges of protein expression [24,103]. This further emphasizes the need for well-constructed DIA analyses of the crevicular fluid.…”
Section: Technical Aspects Of Picf Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common limitation seen in crevicular fluid proteomics is the lack of identification of cytokines, which was often explained by the low absolute abundance of these proteins [12,14]. Targeted approaches may be appropriate for the direct identification of these cytokines, yet DIAbased approaches have also proven to be suited for deeper proteome coverage, especially in cases of high dynamic ranges of protein expression [24,103]. This further emphasizes the need for well-constructed DIA analyses of the crevicular fluid.…”
Section: Technical Aspects Of Picf Proteomicsmentioning
confidence: 99%
“…Differentially adhering proteins were predominantly active in blood coagulation, chemokine and cytokine mediated inflammation and plasminogen activation cascade. Protein identification was neither validated nor was protein adherence assessed in vivo [24].…”
Section: Proteomic Assessment Of Osseointegrationmentioning
confidence: 99%
“…Compared with the no-VTE group, VTE patients received significantly more transfusions of red blood cells (8 [5, 13] vs. 9 [7,13], respectively; P = 0.002) and plasma (5 [2, 9] vs. 7 [4,12], respectively; P = 0.001). Furthermore, compared with no-VTE patients, those who developed VTE had significantly fewer ventilator-free (27 [13,29] vs. 23.5 [12,27], P < 0.01), intensive care unit-free (23 [9,27] vs. 16 [5,23], P < 0.001), and hospital-free days (10 [0, 20] vs. 0 [0, 8], P < 0.001). Interestingly, we observed that patients who did not develop VTE had a significantly higher incidence of in-hospital mortality compared with VTE patients, which could be due to the presence of traumatic brain injury.…”
Section: Patient Demographics and Outcomesmentioning
confidence: 99%
“…Tissue trauma, particularly in the presence of HS, elicits a profound systemic inflammatory response, hallmarked by significant increases in circulating inflammatory mediators with distinct temporal patterns (23). Although past research has demonstrated an augmented proinflammatory response among trauma and HS patients who develop VTE (24), it remains unexplored whether distinct inflammatory mediators are independent predictors of VTE in this population or whether inflammation is directly linked with hypercoagulability.…”
Section: Introductionmentioning
confidence: 99%
“…Organ injury and subsequent development of multiple organ dysfunction syndrome (MODS) is a leading cause of morbidity and mortality following major trauma and hemorrhagic shock (T/HS) (1). While the underlying pathogenesis of MODS after traumatic hemorrhage remains poorly understood, pronounced activation of the coagulation and inflammation systems is evident early in the clinical course and is a known mediator of organ injury in the critically ill (2)(3)(4). The vascular endothelium is a key regulator of thromboinflammation through its expression of an extensive network of anticoagulant and anti-adhesive molecules (5).…”
Section: Introductionmentioning
confidence: 99%